RANCANG BANGUN SISTEM INFORMASI PENGOLAHAN DATA PRAKTIK KERJA INDUSTRI DAN LAPANGAN (STUDI KASUS DI SMK PASUNDAN RANCAEKEK) - Encep Supriatna; Rima Kusmayani Suryaman (Ma'soem University, 2019)
Data processing of industrial and field work practices in SMK Pasundan Rancaekek is still semi manual using a spreadsheet application. This can lead to various problems, namely checking students who have not made payment and registration of PRAKERIN, making evidence of transactions and reports effectively, placing students in accordance with the capacity of the place of PRAKERIN and scheduling supervisors in conducting visits. The method used is the System Development Life Cycle (SDLC), which includes system analysis, system design, system implementation, and system operation. Whereas to analyze user system requirements using Flowmap analysis, Context Diagrams, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), Data Dictionaries, and Structure Charts. The design of the PRAKERIN data processing information system uses Microsoft Visual FoxPro 9.0 as a system implementation, report generation, and for database processing. Thus the system designed by the author is expected to facilitate the PRAKERIN data processing process so that it is more effective and efficient.